Natural radioactivity due to uranium and radon in thermal groundwaters of Central Brazil - Lunardi, M. [UNESP]; Bonotto, D. M. [UNESP] (Springer Nature, 2023)
Hot springs from the Caldas Novas Thermal Complex have been used for balneological purposes since its discovery in the eighteenth century. A detailed analysis has been conducted to investigate the natural radioactivity of these waters due to dissolved 222Rn, 238U and 234U. Sampling campaigns occurred during the dry and rainy seasons to observe how these radioelements are affected by seasonality. Measurements included analyses of alpha-emitting radionuclides, physicochemical parameters and major constituents. Aside from quantitative results, significant correlations were obtained between 222Rn, dissolved oxygen, Eh and sodium, and between 238U, dissolved oxygen, pH, electrical conductivity and calcium. The 234U/238U activity ratio was used as an indirect prospecting tool to indicate whether or not there are potential uranium ore bodies currently forming in this area, and also to demonstrate how mixing of different groundwater masses is occurring.
Keywords: Caldas Novas; Natural radioactivity; Radon; Thermal groundwater; Uranium